A qualitative analysis of patient‐identified adaptive behaviour changes following interdisciplinary Acceptance and Commitment Therapy for chronic pain. (26th January 2018) - Thompson, M.; Vowles, K.E.; Sowden, G.; Ashworth, J.; Levell, J.
Abstract: Background: Interdisciplinary treatment programmes for chronic pain have strong evidence of treatment effect both immediately after treatment and at follow‐up. However, despite strong outcome evidence, it is less clear which specific changes in behaviour are most relevant to patients or to outcomes. Indeed, it is not unknown for clinicians and patients to have different views with regard to goals of treatment. This study sought to evaluate the patients' perspective regarding important behavioural changes that occurred while they were enrolled in a 4‐week interdisciplinary programme of Acceptance and Commitment Therapy (ACT) for chronic pain. Methods: Qualitative data were collected during a treatment session towards the end of treatment. In total, 104 completers from 16 consecutive treatment groups contributed to a data set consisting of 315 unique qualitative comments. Results: Thematic analysis resulted in a theme hierarchy including overarching themes, midlevel themes and subthemes. Three overarching themes were identified as follows: (1) interacting with self – describing an interplay between various aspects of the individual, (2) activity – concerning how individuals practically and sustainably undertook activities and (3) interacting with others – exploring relationships with other people. The results section further describes the midlevel and subthemes that cluster under the overarching themes. Conclusions: These data provide initial insights into the patient's perspective of adaptive behavioural changes gained as part of an interdisciplinary programme of chronic pain rehabilitation. Overall, the data suggest the importance of a mix of both ACT‐specific and more universal coping/pain rehabilitation elements. Future research may examine how these processes relate more directly to treatment outcome. Significance: This study provides new qualitative insights into the patient's perspective of adaptive behavioural changes gained as part of interdisciplinary pain rehabilitation. This and future work may help provide a more detailed understanding of the processes and behaviours that result in successful rehabilitation outcomes.